2020
DOI: 10.1007/s10644-020-09292-7
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic relationship between greenfield investments, cross-border M&As, domestic investment and economic growth in Vietnam

Abstract: This paper investigates the dynamic linkages between different types of foreign direct investment (FDI), domestic investment and economic growth in Vietnam. We decompose the aggregated FDI level into its two major components: greenfield investments, and cross-border mergers and acquisitions (M&As). The empirical results reveal that greenfield investments and cross-border M&As exhibit different impacts on economic growth. While greenfield investments appear to complement domestic investment, which subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 68 publications
2
24
0
2
Order By: Relevance
“…2-5), where the decision of private domestic investors is strongly influenced by economic growth. These results are in line with Chen et al, (2017) and Nguyen et al, (2020) in China and Vietnam, respectively. Furthermore, real investment interest rates has a negative impact on PDI, indicating the crowding-out effect on domestic investment.…”
Section: Table 9 Long-run Coefficients Of Fdisupporting
confidence: 86%
See 1 more Smart Citation
“…2-5), where the decision of private domestic investors is strongly influenced by economic growth. These results are in line with Chen et al, (2017) and Nguyen et al, (2020) in China and Vietnam, respectively. Furthermore, real investment interest rates has a negative impact on PDI, indicating the crowding-out effect on domestic investment.…”
Section: Table 9 Long-run Coefficients Of Fdisupporting
confidence: 86%
“… Check Ashraf and Herzer (2014) andChen et al, (2017), which investigated the effect of entry mode on the FDI-domestic investment nexus in China, as well asNguyen et al, (2020), which analyze the dynamic relationship between greenfield and domestic investments, cross-border M&As, and economic growth in Vietnam.…”
mentioning
confidence: 99%
“…We claim that while greenfield investment aligns with the peace-through-FDI thesis well, cross-border M&A do not. Greenfield investment is highly associated with improved economic conditions (Harms and M eon, 2018;Nguyen et al, 2021;Wang and Wong, 2009) or reduced income inequality (Jensen and Rosas, 2007). Although it may serve as private goods ITPD 6,3 for political leaders, this type of investment is unlikely to negatively affect the provision of public goods.…”
Section: The Onset Of Intrastate Conflictmentioning
confidence: 99%
“…At the same time, export will increase foreign exchange inflow, which will also stimulate economic growth [4]; Gani A(2020) found that China's economic growth has a significant positive impact on Africa, while India's economic impact is not significant [5]; Qamruzzaman, M.(2018) found that financial innovation and economic growth have long-term cointegration. In the long run, financial innovation has a positive impact on economic growth, but the short-term impact is not obvious [6]; Olayungbo D O(2019) found that both long-term and short-term financial development has a positive impact on economic growth [7]; Nguyen H T(2020) found that greenfield investment and cross-border M&A have different effects on economic growth, which is important to the policy of attracting foreign investment [8]; Mohamed Abdouli(2017) found that the inflow of foreign capital can accelerate the economic growth of MENA countries, and the economic growth is easy to cause environmental degradation [9]. Ge L(2020) The model of economic growth in Guangdong-Hong Kong-Macao Greater Bay Area is established by big data mining method.…”
Section: Literature Reviewmentioning
confidence: 99%